The Impact of Culturing the Organ Preservation Fluid on Solid Organ Transplantation: A Prospective Multicenter Cohort Study. (26th April 2019) - Oriol, I; Sabe, N; Càmara, J; Berbel, D; Ballesteros, M A; Escudero, R; Lopez-Medrano, F; Linares, L; Len, O; Silva, J T; Oliver, E; Soldevila, L; et al.
Abstract: Background: We analyzed the prevalence, etiology, and risk factors of culture-positive preservation fluid and their impact on the management of solid organ transplant recipients. Methods: From July 2015 to March 2017, 622 episodes of adult solid organ transplants at 7 university hospitals in Spain were prospectively included in the study. Results: The prevalence of culture-positive preservation fluid was 62.5% (389/622). Nevertheless, in only 25.2% (98/389) of the cases were the isolates considered "high risk" for pathogenicity. After applying a multivariate regression analysis, advanced donor age was the main associated factor for having culture-positive preservation fluid for high-risk microorganisms. Preemptive antibiotic therapy was given to 19.8% (77/389) of the cases. The incidence rate of preservation fluid–related infection was 1.3% (5 recipients); none of these patients had received preemptive therapy. Solid organ transplant (SOT) recipients with high-risk culture-positive preservation fluid receiving preemptive antibiotic therapy presented both a lower cumulative incidence of infection and a lower rate of acute rejection and graft loss compared with those who did not have high-risk culture-positive preservation fluid. After adjusting for age, sex, type of transplant, and prior graft rejection, preemptive antibiotic therapy remained a significant protective factor for 90-day infection. Conclusions: The routine culture of preservation fluid may be considered a tool that provides information about the contamination of the transplanted organ. Preemptive therapy for SOT recipients with high-risk culture-positive preservation fluid may be useful to avoid preservation fluid–related infections and improve the outcomes of infection, graft loss, and graft rejection in transplant patients.